Modelo computacional para simulação da formação do canal de descargas atmosféricas: desenvolvimento e aplicação para monitoramento da evolução das grandezas elétricas envolvidas - Marcelo Augusto Sousa Arcanjo (2018)
This work presents the development and application of a computational model to evaluate the electrical quantities involved in the processes of formation of a CG lightning leader, based on the bidirectional leader model. The model was applied systematically for the interpretation of the effects associated to the processes and for quantification of the evolution of quantities, notably, the potentials developed in the atmosphere, the total electric charge transferred by the discharge and its distribution in the channels, in the ground and in grounded structures, the Electric field at ground level and at the top of the grounded structures, as well as the average current induced in these structures. Real conditions of the occurrences were analyzed, including the incidence at a structure placed on a flat ground and on a mountainous relief. In particular, using the simultaneous measurement and high-speed video data of a real lightning incidence, obtained recently at Morro do Cachimbo Station, the electrical quantities were determined from the geometric trace of this discharge and the results were compared with those of the actual event. The model proved to be consistent and very useful for the development of qualitative and quantitative analyzes, in several cases, that support the interpretation of the processes involved in the formation of negative CG lightning. Results of great interest were obtained for the protection against lightning derived from the application of the model, especially those related to the definition of the radius of attraction of structures. In particular, the estimation of the quotient between the values of average electric field above the top of structures and in the near ground makes it possible to estimate the field threshold associated to the emergence of the upward leader to determine the striking distance parameter.